Outcomes of a novel thin-strut bioresorbable-polymer sirolimus-eluting stent in patients with chronic total occlusions: A multicenter registry. (1st May 2018) - Azzalini, Lorenzo; Demir, Ozan M.; Gasparini, Gabriele L.; Grancini, Luca; La Manna, Alessio; Ojeda, Soledad; Benincasa, Susanna; Bellini, Barbara; Poletti, Enrico; Maccagni, Davide; Soldi, Margherita; Iannetta, Loredana; et al.
Abstract: Background: We aimed to evaluate the mid-term outcomes of a novel thin-strut bioresorbable-polymer sirolimus-eluting stent (BP-SES) in chronic total occlusion (CTO) percutaneous coronary intervention (PCI), as compared with durable-polymer everolimus-eluting stents (EES). Methods: We compiled a multicenter registry of patients undergoing CTO recanalization followed by BP-SES or EES implantation. The primary endpoint was the incidence of target-lesion failure (TLF, a composite of cardiac death, target-vessel myocardial infarction, and target-lesion revascularization) at one year. Propensity score matching (PSM) was used to adjust for case mix. Results: Overall, 413 patients were included (BP-SES n = 242, EES n = 171). PSM resulted in 131 matched pairs, which represented the subject of the main analysis. Antegrade wire escalation was the most successful crossing technique (66% vs. 63%, p = 0.98) in both the BP-SES and EES groups, respectively. Procedural success rates were similar between groups (BP-SES 96% vs. EES 93%, p = 0.24). At one-year follow-up, there were no differences in the primary endpoint of TLF (5.7% vs. 8.3%, p = 0.44), and in cardiac death (0.9% vs. 2.8%, p = 0.32), target-vessel myocardial infarction (0.9% vs 1.9%, p = 0.57), target-lesion revascularization (3.7% vs 3.7%, p = 0.99), or stent thrombosis (0.9% vs. 1.9%, p = 0.57), in BP-SES vs. EES, respectively. Conclusions: Patients undergoing CTO PCI with BP-SES suffer a low rate of TLF at one-year follow-up, which is similar to that of subjects treated with durable-polymer EES. Highlights: CTO PCI with BP-SES was associated with low rates of mid-term adverse events. Patients undergoing CTO PCI with BP-SES suffer a low rate of TLF at one-year. Outcomes of BP-SES were similar to those of the benchmark EES. Rates of adverse events were comparable to those observed in non-CTO PCI.